PERANCANGAN KOMUNIKASI VISUAL PROMOSI KAMPUNG KAIN TUAN KENTANG PALEMBANG - Raden Muhammad Apridho; Aji Windu Viatra; Heri Iswandi (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract : Tourism Village in general is an expression of human life that presents a village tourist destination. In the city of Palembang there is an area of artisan villages where most of the population works as traditional cloth craftsmen. Residents who work as cloth artisans in this village are able to produce various types of typical Palembang fabrics, such as songket, blongsong, tajung, rainbow, or jumputan fabrics of good quality because they are made directly by indigenous people who understand customary values. Palembang city. This design uses the design think planning method which includes premedia, main media and follow-up media. Data collection was carried out through observation, questionnaires, interviews, literature and websites. The data is then identified, classified, selected, then analyzed using the (5W+1H) method, and interpreted according to the text and context. This design aims to promote the Tuan Kentang Fabric Village to the people of Palembang city and outside the city of Palembang. In this design, the resulting media are promotional videos, gates, T-shirts, posters, book catalogs, stickers, tote bags, bucket hats and wallets.